Media Pembelajaran Object Detection Perangkat Jaringan Komputer menggunakan Machine Learning berbasis Desktop - Ervan Wahyu Sri Wijanarko; Ryan Rizki Adhisa (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Learning media is a link between teachers and students so that the process of educational communication interaction between teachers and students can take place in an effective and effective manner. The purpose of this research is to produce a learning media product for object detection of computer network devices using desktop-based machine learning. The type of research used is R&D (Research and Development). This research uses the 4D development model, namely (1) Devine (defining stage) (2) Design (designing stage), (3) Development (development stage) and (4) Disseminate (dissemination stage). Data collection techniques through observation, interviews and questionnaires. This study involved 1 media expert, 1 material expert and respondents of class X students at SMK NU Kunduran as research subjects. The data analysis technique in this study used qualitative analysis. The findings of this research are learning media for object detection of computer network devices using desktop-based machine learning. The research results from the material expert trial received a percentage of 91,25%. Results from media expert trials get a percentage of 90,00%. The results of the student respondents resulted in a percentage score of 84,13%. From these results, it can be concluded that the learning media product for object detection of computer network devices with desktop-based machine learning is said to be feasible to be applied to learning the basics of computer network engineering and telecommunications.